Analisis Pegawai Yang Berkompeten pada PT. Cityneon Prima Mandiri - Oktavian Brahmanvio (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
This research aims to examine the influence of work competency on the performance of PT Cityneon Prima Mandiri employees. This research is a type of quantitative research. The subjects of this research are employees of PT Cityneon Prima Mandiri. and the object in this research is the work competency variable. The population used in the research were all employees of PT Cityneon Prima Mandiri. which amounts to . The instrument used in data collection is a questionnaire which will be given a score based on a Likert scale. This research uses observation and pre-research methods involving one variable. The results of this research show that work competency has a positive and significant influence.